Epidural Volume Extension (EVE) - Mahmud; Wijaya, Indriyani (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Epidural Volume Extension (EVE) technique injects normal saline into the epidural chamber immediately after injection of local anesthesia into the intrathecal (or after subarachnoid/spinal block). Normal saline injection would widen the epidural space thus making the spread of local anesthesia in previous intrathecal injections and the distribution of cerebrospinal fluid to be higher (more cephalad), or it could be said that this EVE technique utilizes the volume effect of normal saline that decreases the volume of intrathecal space. The EVE technique may be useful for reducing the dose of local anesthesia injected intrathecally while still achieve an adequate block height for surgery, as well as for faster recovery of motor blockades. Unfortunately, for the risk of hypotension, the EVE technique does not significantly reduce this risk. Hypotension persists even though the hemodynamics (arterial blood pressure drop mean) is observed to be more stable.